STUDI KOMPUTASI REAKSI ADSORBSI DISOSIASI GAS O 2 PADA PERMUKAAN Pt-Fe DENGAN METODE TEORI FUNGSI KERAPATAN - Darmin -; Rahmat Gunawan; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2013)
Platinum purpose as a catalysts on the cathode in a fuel cell hydrogen system gets a role in disconnection of O 2 molecules. Power adsorption and dissociation of O 2 molecules determined the effectiveness and efficiency of the nature of catalyst that is utilized. All thid time metal is considered the most effective as a catalyst in fuel cells hydrogen is Pt. After be done investigation and calculation is known about platinum and iron alloy (Pt-Fe) can be utilized as a catalyst that has approached the effectiveness and efficiency of pure Pt metal. One of the way to determine the effectiveness and efficiency of the catalyst Pt-Fe alloys by calculating the value of the potential energy surface (PES). PES value calculation is done using density functional theory calculations. Analysis’s result point out the value of the potential energy surface (PES) O 2 molecules in the Pt-Fe metal fusion for -929.8341 Ry with optimal distance of 2.4908 A of Pt-Fe’s metal surface and distances among O atoms as big as 3.3211 A.